Institutions and behavior: Experimental evidence on the effects of democracy - Pedro Dal Bó; Andrew Foster; Louis Putterman (Brown University, Department of Economics, 2007)
We present results from a novel experiment on the effect of a policy designed to encourage cooperation in a prisoner's dilemma game. We find that the effect of this policy on the level of cooperation is greater when it was chosen democratically by the subjects than when it was exogenously imposed. This difference remains after controlling for selection (those that choose the plicy may be more likely to be affected by it). We conclude that the treatment effect of policies may depend on whether they are endogenous or exogenous to the society on which they are imposed. Therefore, democratic institutions may have an effect on behavior in addition to the effect in terms of policy choice. More generally, our findings have implications for empirical studies of treatment effects in other contexts: the effect of a treatment may depend on whether it is endogenous or exogenous.
Keywords: C1; C9; D7; O1; 330; Institutions; democracy; cooperation; endogenous treatment effect; Institutionalismus; Politisches System; Verhaltensökonomik; Kooperation; Theorie